Market Access and Quality Upgrading: Evidence from Four Field Experiments. A Replication Study of Bold et al. (American Economic Review, 2022) - Ryan McWay; Karim Nchare; Pu Sun (Journal of Comments and Replications in Economics (JCRE), 2024)
Bold et al. (2022b) investigate the effect of providing access to a larger, centralized market where quality is rewarded with a premium on farm productivity and framing incomes from smallholder maize farmers in western Uganda, using a series of randomized experiments and a differencein-differences approach. We successfully reproduce the results of this study using the publicly provided replication packet. Then test the robustness of these results by re-defining treatment and outcome variables, testing for model misspecification and the leverage of outliers, and testing for non-random selection in the Fisher-permutation process. Our results show that the findings in Bold et al. (2022b) are robust to a variety of decisions in the research process. This evokes confidence in the internal validity of the findings.
https://doi.org/10.15456/j1.2023270.1716216104
Keywords: L14; L15; O13; Q12; Z00; 330; Reproducibility; Replication; Farm Productivity; Economic Development